Analisis Peran Komunikasi dalam Promosi Badan Amil Zakat Nasional (BAZNAS) Kota Tangerang: Studi Kasus Sosialisasi Zakat Fitrah Dan Zakat Maal di Kecamatan Karawaci - Agustine, Annisa Dwi; Suseno, Ari; Fournawati, Sri Murdilah (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research aims to find out the role of communication in the promotion of the Tangerang City National Amil Zakat Agency (BAZNAS) Tangerang City. This research was conducted at Baznas Tangerang City from February to July 2024. This research used a case study qualitative research method. The author uses observation, interview and documentation techniques to collect data. Data analysis consists of data reduction, data presentation, and drawing conclusions. Based on the research results, in carrying out the role of communication for promotion, there are strategies that might be able to attract new muzakki at BAZNAS Tangerang City, and these strategies are also important tools to implement. This research uses IMC (Integrated Marketing Communication) theory. Based on the results of the research that the author obtained, in practice at BAZNAS Tangerang City, when the socialization was carried out the role of communication media well, and implemented all the indicators contained in it, and was also able to inform the muzakki and many people who learned new things about zakat, as well as educate the public about paying zakat Fitrah and Zakat Maal, and several obstacles that can arise from several factors.